THE ROLE OF MARKETING INFORMATION SYSTEMS (MKIS) IN SERVICE QUALITY IN ETHIOPIAN INDUSTRIES - Berhan, E.; Kitaw, D. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This paper deals with the role of marketing information systems for service quality in Ethiopian industries in terms of their IT infrastructure, data acquisition, information processing, business function, and service quality. A quantitative survey of 42 Ethiopian industries in 2009 indicated that most of these industries are dominated by noncomputerised information systems. The data acquisition and IT infrastructure strongly support the information process. Information processing significantly and positively predicts both service quality and business function. But the business function that uses processed data and information for its activities